Biossíntese de nanopartículas de prata sintetizadas a partir de sobrenadante livre de células de Pediococcus acidilactici CE51 e avaliação do seu efeito em biofilmes de Listeria monocytogenes - Gervasoni, Letícia Franco (2025)
Listeria monocytogenes is the etiological agent of listeriosis, a severe disease with high mortality, especially in immunocompromised individuals. Its ability to form biofilms in food industrial environments makes it challenging to eliminate with sanitizers and increases the risk of contamination in ready-to-eat foods. Alternative strategies, such as the use of silver nanoparticles (AgNPs) associated with bacteriocins, have shown potential in combating bacterial biofilms. The aim of this study was to synthesize silver nanoparticles using the cell-free supernatant (CFS) of Pediococcus acidilactici CE51 and evaluate their effectiveness against L. monocytogenes biofilms. The CFS from Pediococcus acidilactici CE51 was produced and used for the biosynthesis of silver nanoparticles (Bac-AgNPs). The Bac-AgNPs obtained were characterized by Dynamic Light Scattering (DLS), Polydispersity Index (PDI), Zeta Potential, UV-Vis spectrophotometry, and their antimicrobial activity was assessed through serial dilution in microtiter plates to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Acute toxicity was tested on Galleria mellonella larvae, and the stability of Bac-AgNPs was analyzed under different pH, temperature, and CFS ratio conditions. The effect of Bac-AgNPs on the formation and dispersion of L. monocytogenes biofilms was also investigated. Statistical analyses were performed, and significant differences were established at p < 0.05. The synthesized Bac-AgNPs (164 mg/mL) presented a size of 131.8 nm, PDI of 0.28, Zeta Potential of -19.7 mV, and a maximum absorbance peak at 420 nm. In toxicity tests, Bac-AgNPs and CFS did not affect the survival of Galleria mellonella. For L. monocytogenes, the MIC was 82 mg/mL, and the MBC was 164 mg/mL, with a reduction of 3.06 log CFU/mL at 82 mg/mL. No antimicrobial effect was observed for other tested strains. In stability assays, Bac-AgNPs maintained antimicrobial activity at pH 2 and 7 but not at pH 9. Bac-AgNPs in a 1:10 ratio with CFS showed better antimicrobial results. After 7 days of storage, antimicrobial efficacy decreased, particularly for Bac-AgNPs stored at 4°C. In biofilm treatment, Bac-AgNPs alone were ineffective during the initial hours; however, when combined with CFS, they caused a significant reduction in bacterial counts after 6 hours, with up to a 2.5 log CFU/mL reduction after 24 hours. Bac-AgNPs synthesized from the CFS of P. acidilactici CE51 demonstrated strong antimicrobial potential against L. monocytogenes and its biofilms, with good biocompatibility and synergistic efficacy with CFS, though adjustments are required to optimize long-term stability.